2006
DOI: 10.1080/07315724.2006.10719525
|View full text |Cite
|
Sign up to set email alerts
|

Whole Cinnamon and Aqueous Extracts Ameliorate Sucrose-Induced Blood Pressure Elevations in Spontaneously Hypertensive Rats

Abstract: Cinnamon is used for flavor and taste in food preparation, but cinnamon may have additional roles in glucose metabolism and BP regulation. Therefore, BP regulation may not only be influenced favorably by limiting the amounts of dietary substances that have negative effects on BP and insulin function but also by the addition of beneficial ones, such as cinnamon, that have positive effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 38 publications
3
41
0
1
Order By: Relevance
“…Cinnamon supports healthy circulation by bringing blood from the center of the body to the skin. Results obtained from use of animals as case studies are also indicative of the ability of cinnamon to regulate blood pressure via peripheral vasodilatation [24]. This mechanism may have caused increased eGFR in the cinnamon supplementation group and may be consistent with the hypothesis of the renal cause of essential hypertension, although it can also be explained by renal damage caused by elevated BP.…”
Section: Discussionsupporting
confidence: 55%
“…Cinnamon supports healthy circulation by bringing blood from the center of the body to the skin. Results obtained from use of animals as case studies are also indicative of the ability of cinnamon to regulate blood pressure via peripheral vasodilatation [24]. This mechanism may have caused increased eGFR in the cinnamon supplementation group and may be consistent with the hypothesis of the renal cause of essential hypertension, although it can also be explained by renal damage caused by elevated BP.…”
Section: Discussionsupporting
confidence: 55%
“…In addition to its culinary uses, cinnamon has been used in traditional herbal medicine to treat different health conditions (Gruenwald et al, 2010). Some studies showed that cinnamon extracts and its constituents also effective in the treatment of cancer (Nishida et al, 2003), insecticidal (Yang et al 2005), hypotensive (Preuss et al, 2006), antioxidant and antimutagenic activities (Jayaprakasha et al, 2007), cholesterol-lowering effects (Subash Babu et al, 2007), antimicrobial action (Carmo et al, 2008) and anti-inflammatory effect (Tung et al, 2008). The liver is the largest internal organ in the body and played a very important role in the detoxification of harmful and toxic substances.…”
Section: Introductionmentioning
confidence: 99%
“…The antihypertensive action of cinnamon extract was successfully demonstrated in both spontaneously hypertensive rats [14] and patients with metabolic syndrome (22 men and women treated with a 500-mg extract daily for 12 weeks) [15]. Moreover, triglyceride-lowering effects with cinnamon were observed in Wistar rats fed a high-fructose diet [16] and in some clinical trials.…”
Section: Presl (Lauraceae)mentioning
confidence: 83%